Effects of long‐term care setting on spousal health outcomes. (23rd September 2018) - Dong, Jing; Pollack, Harold; Konetzka, Rita Tamara
Abstract : Objective: To provide empirical evidence on the effects of home and community‐based services (HCBS) (vs nursing home) use on spousal health. Data Sources: Merged data from the 1996 to 2012 Health and Retirement Study (HRS) and the Area Health Resource File (AHRF). Study Design: We assess the impact of HCBS use on spousal health. We use an instrumental variable (IV) approach to account for the potential endogeneity of the choice of care setting and reverse causality. Our instrument is the supply of skilled nursing home beds per 1000 people older than 65 years. Data Extraction Methods: Our sample includes spouses of HCBS or nursing home users, resulting in 8608 observations. Principal Findings: We find that HCBS use leads to harmful effects on spousal physical health, which may be caused by increased informal care responsibilities. We also find improved spousal mental health, especially in depression symptoms, which may be caused by increased satisfaction. Conclusions: We find evidence of both beneficial (mental health) and harmful (physical health) consequences for spouses of individuals receiving LTC at home relative to in an institution. Our results are important in estimating the potential cost and effectiveness of HCBS expansion.